2018
DOI: 10.1007/s40496-018-0194-y
|View full text |Cite
|
Sign up to set email alerts
|

Growth Factors and Cell Homing in Dental Tissue Regeneration

Abstract: Purpose of Review To summarize current views on the role and therapeutic potential of growth factors (GFs) within endodontic cell homing. Recent Findings Cell homing/revitalization techniques aim to regenerate dentin and pulp using endogenous cells. Clinically, revitalization has successfully created new vital tissue in necrotic permanent teeth with an open apex; however, there is no evidence of new odontoblasts, pulp tissue, or predictable extension in root length. Although the response is reparative rather… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 108 publications
0
45
0
4
Order By: Relevance
“…Although the scope of RE is presently limited to the management of immature nonvital permanent teeth. [ 3 ] Research is underway to attain pulp regeneration in mature teeth,[ 22 ] which, if achieved, would revolutionize the field of Endodontics and be beneficial to patients and the public health sector. “Seal Bio” a nonobturation technique was among the initial efforts to practice regeneration in mature permanent teeth.…”
Section: Discussionmentioning
confidence: 99%
“…Although the scope of RE is presently limited to the management of immature nonvital permanent teeth. [ 3 ] Research is underway to attain pulp regeneration in mature teeth,[ 22 ] which, if achieved, would revolutionize the field of Endodontics and be beneficial to patients and the public health sector. “Seal Bio” a nonobturation technique was among the initial efforts to practice regeneration in mature permanent teeth.…”
Section: Discussionmentioning
confidence: 99%
“…They inferred that the vasculature could provide support for cell survival and differentiation, and thus long-term dentinogenesis in dentin-pulp complex [3,11]. In addition, real-time PCR analysis revealed that the expression of OCT4 gene was lower in the inflamed pulp; however, the expressions of other embryonic and dentinogenic genes in the inflamed pulp were similar to those in the normal pulp.…”
Section: Discussionmentioning
confidence: 99%
“…It is established that dental tissue repair processes can be signaled by bioactive molecules released from the dentin by cariesderived bacterial acids or restorative agents, such as calcium hydroxide and calcium silicates. Because of the biphasic signaling that occurs in response to molecules, such as TNFa and TGF-b1, along with ROS and bacterial components, it is apparent that a fine balance exists between pathogenesis and dental tissue repair [22][23][24][25][26][27][28] .…”
Section: Significancementioning
confidence: 99%